Potensi Penerimaan Pajak Bumi dan Bangunan Sektor Perdesaan dan Perkotaan di Kabupaten Batang Hari - Rama Adi Putra; Arman Delis; Siti Hodijah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2015)
This research aims at looking at levels of growth, contribution, potency and projection of income from Land and Building Tax (PBB) in rural and urban sectors in Batang Hari Distric. The analysis instruments used are : growth, contribution, potency analysis and projection. Analysis result shows  that the average of income growth of Land and Building Tax in rural and urban sectors since observation period is  9,67% ; and the contribution  of Land and Building Tax in rural and urban sectors to Budget of Local revenue and Expenditure (APBD) is only in the average of 0,89%, meaning that it is still low. Whereas  the average targetted is 59,34% of the known potency. This means that the target can be increased.  Furthermore, in accordance with estimates projection result for  2014-2020 get increased. This means that the income prospect will continuonsly increase The growth of income will be better if data collection is accurately carried out every year ; human resources of this division is increased; and coordination is continuously improved.